Student centred teaching and motivation - Mullamaa, Kristina (Advances in Social Sciences Research Journal, 2017)
The modern learning environment offers great opportunities for educators and teachers to apply the principles of innovative learning and teaching. In this article we view some relevant aspects of motivation and individualisation as analysed in recent research. We review the following topics: conscious and subconscious motivation; mastery and performance goals, teachers´ role as advisers, as well as motivation and the learning context. We approach the topic through the prism of examining the possibilities for supporting and encouraging student-centred learning, as well as increasing student responsibility in their learning process. The focus is on how individualisation and increased responsibility affect students´ motivation and thus their capacity to become successful and independent life-long learners. As an illustrative example of how students view the paradigmatic changes, we present the results from our current research project on student-centred learning.